Exhumation history of the Andean broken foreland revisited - Davila, Federico Miguel (2013)
The Andean broken foreland in west-central Argentina, located 400–800 km from the Peru-Chile Trench is associated with fl at subduction linked to collision of the oceanic Juan Fernandez Ridge. While the conditions associated with fl at subduction would be expected to produce increases in rock uplift and exhumation, where thrusting and dynamic forces work together, a prevalence of pre-Cenozoic apatite fi ssion track (AFT) cooling ages suggests that there is no such link. The lack of Cenozoic cooling ages is at odds with structural reconstructions and basin studies along the foreland that show several kilometers of exhumation. This paradox can be reconciled by taking into account the thermal effects of fl at subduction that removed the mantle wedge, and a signifi cant source of heat fl ow into the crust. Reinterpretation of published AFT exhumation data (>320 ages) using more realistic lower geothermal gradient values allows for substantial exhumation and explains the lack of Cenozoic exhumation ages across the foreland region.